Kurikulum Pendidikan Dasar: Konsep, Landasan, dan Prinsip Pengembangannya - Syaifuddin, Ahmad (Jurnal Ilmiah Madrasah, 2025)
ABSTRACTCurriculum development is a strategic process that plays an important role in improving the quality of education, especially at the elementary education level. This article aims to theoretically examine the concepts, foundations, and main principles in curriculum development, as well as their relevance to curriculum implementation in elementary education. The research method used is a literature review, by analyzing various relevant literature sources such as books, scientific journals, and education policy documents. The results of the study indicate that curriculum development must be based on philosophical, psychological, and sociological foundations and pay attention to the principles of flexibility, relevance, continuity, and efficiency. The elementary education curriculum needs to be designed not only to meet academic demands, but also to shape the character of students from an early age. This article is expected to be a reference for educators, curriculum designers, and policy makers in developing a visionary and contextual curriculum.Keywords: Curriculum Development; Elementary Education Curriculum; Library StudiesABSTRAKPengembangan kurikulum merupakan proses strategis yang berperan penting dalam peningkatan mutu pendidikan, khususnya di jenjang pendidikan dasar. Artikel ini bertujuan untuk mengkaji secara teoritis mengenai konsep, dasar, dan prinsip-prinsip utama dalam pengembangan kurikulum, serta relevansinya terhadap implementasi kurikulum pada pendidikan dasar. Metode penelitian yang digunakan adalah kajian pustaka, dengan menganalisis berbagai sumber literatur yang relevan seperti buku, jurnal ilmiah, dan dokumen kebijakan pendidikan. Hasil kajian menunjukkan bahwa pengembangan kurikulum harus berpijak pada landasan filosofis, psikologis, dan sosiologis serta memperhatikan prinsip fleksibilitas, relevansi, kontinuitas, dan efisiensi. Kurikulum pendidikan dasar perlu dirancang tidak hanya untuk memenuhi tuntutan akademik, tetapi juga membentuk karakter peserta didik sejak dini. Artikel ini diharapkan dapat menjadi rujukan bagi pendidik, perancang kurikulum, dan pengambil kebijakan dalam menyusun kurikulum yang visioner dan kontekstual.Kata-Kata Kunci: Pengembangan Kurikulum; Kurikulum Pendidikan Dasar; Kajain Pustaka